Konsep Kompetensi Pedagogik Guru dalam Kitab Ushul Al Tarbiyah Wa Al Ta'lim - Bahruddin Bahruddin; Ahmad Ahmad; Abdul Khalim (Cakrawala Repositori IMWI, 2023)
Educational goals can be achieved with a harmonious relationship between educational components including teachers and their pedagogical competence. Pedagogic competence is also found in the book Ushul Al Tarbiyah Wa Al Ta'lim. So the researcher wants to study more about the concept of Teacher Pedagogic Competence in the Book of Ushul Al Tarbiyah Wa Al Ta'lim. The purpose of this research is to obtain information about the concept of pedagogical competence in the book Ushul Al Tarbiyah Wa Al Ta'lim. The research method was carried out by means of a literature study on the book Ushul Al Tarbiyah Wa Al Ta'lim volumes I, II, III, and IV so that the results obtained were that pedagogic competence has components that must be mastered, namely: (1) The teacher must always have the attitude to work hard also never give up in carrying out learning, (2) Each teacher must be able to understand various theories of general knowledge in education such as meaning, phenomena and educational goals, (3) Teachers must be able to understand the various characteristics of their students (4) Teachers in Islamic boarding schools must have an understanding of how to carry out learning with appropriate methods and materials, (5) Teachers must have an understanding of how to develop the potential of students, (6) Teachers in epsantrean must have an understanding in providing learning (7) Teachers must be able to communicate effectively, full of concern and courtesy to students, (8) Every teacher must have the ability to conduct assessments and evaluations for their students (9) Each teacher must be able to be a role model for each of his students, (10) Teachers not only carry out tutoring but also provide guidance in worship and increase faith.